2022
DOI: 10.1155/2022/4462018
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Study of the Effects of Air Pollution and Weather in Respiratory Disease Patients Visiting Emergency Departments

Abstract: Background. To date, investigating respiratory disease patients visiting the emergency departments related with fined dust is limited. This study aimed to analyze the effects of two variable-weather and air pollution on respiratory disease patients who visited emergency departments. Methods. This study utilized the National Emergency Department Information System (NEDIS) database. The meteorological data were obtained from the National Climate Data Service. Each weather factor reflected the accumulated data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…This was achieved by developing a new chaos equation using patient data and weather predictions that have been gathered. The findings of this study agree with previous studies that have linked weather data to respiratory disease cases (Lee et al 2022;Bhat et al 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was achieved by developing a new chaos equation using patient data and weather predictions that have been gathered. The findings of this study agree with previous studies that have linked weather data to respiratory disease cases (Lee et al 2022;Bhat et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The daily projected patient count and the output of the new chaotic equation had a strong correlation of 90.16% after the chaotic system's equations were solved. As a result, the findings of this study are in line with those of other studies that have evaluated the effectiveness of time series in forecasting the occurrence of respiratory diseases (Shaman and Kohn 2009;Lee et al 2022). This study reported a higher performance measure, with a correlation of 90.16% between real patient cases and predicted data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding meteorological factors, previous studies have suggested that temperature, humidity, air pressure and other meteorological conditions affect the incidence of respiratory diseases and the number of medical visits [25,26], and exposure to low and high temperatures increase the risk of disease [27]. In addition, in a previous study, the incidence of respiratory diseases caused by high temperature exposure was higher than that caused by low temperature exposure; however, the incidence of respiratory syncytial virus (RSV) infection was related to low temperature exposure [28].…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…Moreover, there was a lagged effect of air pollutants on the incidence of influenza. Recent studies on the correlation between the influenza incidence and air pollutants have mostly applied statistical models, such as correlation analysis (30), regression analysis (30), machine learning (31), and non-linear models (32). To the best of our knowledge, few studies have developed and applied sensitivity analysis to examine the relationship between disease and environment.…”
Section: Introductionmentioning
confidence: 99%